Multiple antiphospholipid antibodies positivity and antiphospholipid syndrome criteria re-evaluation. (October 2014) - Forastiero, R
The antiphospholipid syndrome (APS) is characterized by the presence of aPL and thrombosis and/or pregnancy morbidity. The last APS laboratory classification criteria include the presence of at least one of the antiphospholipid antibodies (aPL) [lupus anticoagulant (LA), anticardiolipin (aCL) and/or anti-β2 glycoprotein I antibodies (aβ2GPI)] and introduced the concept of subclassification of APS patients into two different categories of aPL assay positivity (combination or single aPL). Several studies have recently shown that the risk for thrombosis increases with each additional aPL detected. We found that the presence of IgG antibodies to β2GPI and/or prothrombin increased thrombotic risk in patients with LA and/or aCLin a prospective study. Various studies have recently demonstrated that patients with triple positivity (LA, aCL and aβ2GPI) are at the highest risk for venous and arterial thrombosis and for obstetric complications. In retrospective but also in prospective studies the rate of thrombotic recurrence was high in subjects with triple positivity even while on anticoagulant therapy. In addition, the occurrence of a first thrombotic event in asymptomatic carriers of triple positivity was higher than in those with single aPL positivity. The inclusion of the detection of antibodies against domain I of β2GPI and/or antibodies to prothrombin would probably help to further identify more clinically relevant aPL. Based on the last findings, there are some proposals to consider only patients with triple positivity as definite APS (thrombotic and obstetric).